CHECKPOINT INHIBITOR IMMUNE THERAPY: Systemic Indications and Ophthalmic Side Effects. Issue 6 (June 2018) - Dalvin, Lauren A.; Shields, Carol L.; Orloff, Marlana; Sato, Takami; Shields, Jerry A.
Abstract : Purpose: To review immune checkpoint inhibitor indications and ophthalmic side effects. Methods: A literature review was performed using a PubMed search for publications between 1990 and 2017. Results: Immune checkpoint inhibitors are designed to treat system malignancies by targeting one of three ligands, leading to T-cell activation for attack against malignant cells. These ligands (and targeted drug) include cytotoxic T-lymphocyte antigen-4 (CTLA-4, ipilimumab), programmed death protein 1 (PD-1, pembrolizumab, nivolumab), and programmed death ligand-1 (PD-L1, atezolizumab, avelumab, durvalumab). These medications upregulate the immune system and cause autoimmune-like side effects. Ophthalmic side effects most frequently manifest as uveitis (1%) and dry eye (1–24%). Other side effects include myasthenia gravis (n = 19 reports), inflammatory orbitopathy (n = 11), keratitis (n = 3), cranial nerve palsy (n = 3), optic neuropathy (n = 2), serous retinal detachment (n = 2), extraocular muscle myopathy (n = 1), atypical chorioretinal lesions (n = 1), immune retinopathy (n = 1), and neuroretinitis (n = 1). Most inflammatory side effects are managed with topical or periocular corticosteroids, but advanced cases require systemic corticosteroids and cessation of checkpoint inhibitor therapy. Conclusion: Checkpoint inhibitors enhance the immune system by releasing inhibition on T cells, with risk of autoimmune-like side effects. Ophthalmologists should include immune-related adverse events in their differential when examining cancer patients with new ocular symptoms. Abstract : Checkpoint inhibitors are medications initially used to treat previously incurable cutaneous melanoma metastasis through T-cell immune modulation. These drugs, now used for several malignancies, have associated ocular side effects, especially autoimmune-like inflammatory conditions. With increasing frequency of use, ophthalmologists should be aware of these medications and potential side effects.